Modeling mystery - Wood, W (Uniwersytet Mikołaja Kopernika w Toruniu, 2016)
The practice of model-building is very common in analytic philosophical theology. Yet many other theologians worry that any attempt to model God must be hubristic and idolatrous. A better understanding of scientific modeling can set the stage for a more fruitful engagement between analytic theologians and their critics. I first present an account of scientific modeling that draws on recent work in the philosophy of science. I then apply that account to a prominent analytic model of the trinity, Michael Rea and Jeffrey Brower’s “material constitution model.” I argue that modeling—whether scientific or theological—need not be understood as a hubristic enterprise. A model does not always try to grasp its target at all, let alone grasp it fully and completely. Even theologians who are committed to a strong doctrine of divine mystery can therefore find value in analytic modeling.